Novel PDE6B Mutation Presenting with Retinitis Pigmentosa – A Case Series of Three Patients - Palmowski-Wolfe, Anja; Stingl, Katarina; Habibi, Imen; Schorderet, Daniel; Tran, Hoai Viet (Klinische Monatsblätter für Augenheilkunde, 2019)
Background Retinitis pigmentosa (RP) affects 2.5 million people worldwide. Increased identification of causative gene defects and the increasing possibility of treatment necessitates better knowledge of phenotype-genotype correlations to help identify patients who would benefit from targeted gene therapy and improve patientsʼ care. Here, we report on three RP patients with mutations in the PDE6Β Gene that have not been described previously.History and Signs Three patients with a PDE6Β mutation were identified: 1. A 30-year-old male with a homozygotous mutation (c.[2351dupA],[2351dupA], p.[Q785Gfs*20],[Q785Gfs*20]) who was followed for 8 years. 2. A 54-year-old Caucasian woman with a heterozygous mutation [p.(K611Nfs*6), p.(Q567*)] who was followed for 40 years. 3. A 46-year-old Caucasian male [p.(E271K), p.(R627_E631del)]. All had noted an onset in childhood and complained of night blindness and photophobia. Typical bone spiculae were seen, and peripheral visual fields were progressively affected in all patients. Ganzfeld-ERG showed typical signs of rod-cone dystrophy. Patients 1 and 2 underwent cataract surgery at ages 27 and 36 years with an improvement in vision, while patient 3 had not developed a cataract at age 54.Conclusions In children complaining of night blindness, a PDE6Β-associated RP needs to be taken into consideration. Apart from helping patients with optical aids, such as polarizing filters or magnification, a specific diagnosis is especially important in view of emerging genetic treatment options. In particular, in RP patients with a PDE6Β mutation, a phase I/II study is currently ongoing (https://clinicaltrials.gov/ct2/show/NCT03328130).
Keywords: retina; electrophysiology; genetics; PDE6B; retinitis pigmentosa; phenotype; genotype; novel mutation